METHODS OF POSTPARTUM BLOOD LOSS MEASUREMENT IN INDONESIA SHOULD BE MODIFIED FOR BETTER ACCURACY: A LITERATURE REVIEW - Siska Febrina Fauziah; Melyana Nurul Widyawati; Tecky Afifah Santy Amartha (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Backgrounds: Assessment of blood loss after delivery is important because intervention in the “golden hour” is crucial to prevent maternal morbidity and mortality. In fact, the biggest obstacle in overcoming postpartum blood loss are symptom recognition, accuracy, and timely diagnosis. Aims: The objective of this study was to analyze the strengths and weaknesses between visual estimation and quantification of blood loss measurements. Methods: Literature review was conducted using the electronic databases Science Direct, Pubmed, and Google Scholar. Measurement of blood loss and postpartum hemorrhage was used as keywords in searching strategy. A total of 23 from 17.200 of publications range from 2010 until May 2017 and presented in English language were included in this review. Results: Many studies show that quantification of blood loss method is better than visual estimation. Visual estimation of blood loss was imprecise, tend to underestimate blood loss, and thus to delay diagnosis of PPH, whilst quantification of blood loss more accurate and objective. Nonetheless, quantification methods not used routinely due to their unavailability, more time consuming, complicated, costly, and analyst workload increases. Conclusions: Modified measurement method and its existing protocol needed to overcome blood loss during postpartum.